PERNIKAHAN KRISTEN DALAM PERSPEKTIF FIRMAN TUHAN - Seri Antonius (Universitas Asahan, 2020)
This article is a literature study that describes the concept of Christian marriage in the view and teaching of God's word. To explain this, the author gives various information from library sources related to the research topic which was then described descriptively. From the research carried out, the concept of Christian marriage taught by the word of God is different from the concept of happiness based on human views in general. Understanding of the meaning of marriage in Christianity today has experienced a shift and seems to have been narrowed down with various understandings that are not in accordance with the nature and understanding of marriage in the Bible. Some understand getting married and forming a household because of several factors and one of them is because of age or peers they are all married and have children. God's Word clearly states and reveals God's plan and design for a new household. Keywords: the concept of Christian marriage, submission, love